Relationship between level of knowledge about menopause with anxiety in elderly women aged 45-54 years at drajat health center Cirebon city - Fauziah, Eva (Jurnal EduHealth, 2024)
Menopause is the final stage of a woman's reproductive period. Women who will enter menopause will experience physical and psychological. If this is not handled properly it will cause anxiety. Based on preliminary studies conducted on 10 menopausal mothers aged 45-54 years who came to the elderly posyandu at Drajat Health Center Cirebon City they felt various complaints such as irritability, and stress. This study aims to determine the relationship between the level of knowledge about menopause and anxiety in elderly women aged 45-54 years at Puskesmas Drajat. This type of research is quantitative with a cross sectional design. The sample in this study amounted to 93 respondents aged 45-54 years who were experiencing menopause from a total population of 103 respondents obtained through simple random sampling. data collection using the Hamilton Rating Scale for Anxiety (HRSA) questionnaire and knowledge level questionnaire. Data analysis using chi square test at α 0.05. The results showed mild anxiety as many as 36 respondents (38.7%), respondents who experienced moderate anxiety were 15 respondents (16.1%) and respondents who experienced severe anxiety were 42 respondents (45.2%). The results of the chi square test show that there is a relationship between knowledge and anxiety during menopause with the results of a p value of 0.000 and a value of R = 0.425. Health workers are expected to be able to improve health services, especially for premenopausal women, not only physical problems but also psychological problems.